Evaluation of the composition of electronic waste hard disk using spectroanalytical techniques: proposition of fast and simple methods - Castro, Jeyne Pricylla de (Universidade Federal de São Carlos, 2020)
The electronic waste is a worldwide problem of great magnitude with 53.6 Mt of waste generated in 2019. Unfortunately, the recycling rate is still very low. It is estimated that only 2% of the electronic waste is recycled in Brazil, being a situation far from ideal. There are many factors that can influence recycling, being the complexity of these materials a critical aspect. Therefore, the analytical chemistry can assist in all this process, optimizing and developing new methods. The purpose of this thesis was the development of characterization procedures of high-performance magnets and printed circuit board samples from hard disk of computer. Three analytical techniques were used: Inductively coupled plasma optical emission spectroscopy (ICP OES), Laser-induced breakdown spectroscopy (LIBS) and Wavelength dispersive x-ray fluorescence (WD XRF). So, softer reference methods were developed using ICP OES, where the results were used to the proposition of methods more quick, simple and “green” using the techniques of direct analysis of solids (LIBS and WD XRF). In this context, different calibration approaches were studied and, in this thesis was proposed a new strategy named by two-point calibration transfer (TP CT). In addition, parallel factor analysis (PARAFAC) was used for the first time in the characterization of spectra LIBS from the analysis of printed circuit board, being a promising approach for the LIBS technique.
Avaliação da composição de discos rígidos de resíduos eletrônicos utilizando técnicas espectroanalíticas: proposição de métodos rápidos e simples
Keywords: Resíduo eletrônico; Estratégias de calibração; Mineração urbana; Análise direta de sólidos; LIBS; WD XRF; ICP OES; Electronic waste; Calibration strategies; Urban mining; Direct analysis of solids; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA